Retrospective longitudinal analysis of the effects of postnatal weight gain on the timing and tempo of puberty and menarche in a cohort of Italian girls - Vittorio Ferrari; Simona Stefanucci; Marta Ferrari; Daniele Ciofi; Stefano Stagi; on the behalf of the Tuscany Menarche Study Group (BMC, 2022)
Abstract Objective over the last few decades there has been a progressive decline in the average age of onset of pubertal development stages in both sexes. The increase in the prevalence of childhood obesity seems to play an important role in this phenomenon. Design we undertook a retrospective, longitudinal evaluation of the average age of thelarche and menarche to evaluate the relationship between BMI and weight change during the first years of life and the timing and tempo of puberty. Methods we evaluated data for 577 Italian girls born between 1995 and 2003. We collected the main auxological and clinical parameters, including age at B2 and at menarche, BMI SDS at B2 and menarche, gestational age and birth weight and Z-score change from birth weight (BW) to BMI at B2 and menarche. Results the mean age of B2 was 10.06 ± 1.03 years and the mean age of menarche was 12.08 ± 1.02 years. Age at B2 and menarche were inversely correlated with BMI SDS (p < 0.0001). Both age at menarche and at thelarche have an inverse relationship with the Z-score change from birth weight and BMI at menarche and thelarche respectively (p < 0.0001). Conclusions our data confirm a significant relationship between BMI and age of B2 and menarche. We observed a clear relationship among weight change during the first years of life, age at thelarche and menarche and the duration of puberty, demonstrating the importance of weight and weight gain in determining the timing and tempo of pubertal changes and growth.